TUJUAN PENDIDIKAN ISLAM DALAM PERSPEKTIF ALQURAN - Hasibuan, Nasruddin (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2014)
Islamic as relegion have the quality universally and comprehensive had arranged all aspect of life, included educational. Islamic exhausted values of education as high priority and noble, so that to islamic people always motivate in order that study and learned, because the people leraned knowledge will get noble position in side of the Allah SWT (god). Education constitute key word for every human so that he/she get knowledge. however with education science will got and reserved goodly. No amazed if now government compulsory of study program nine years so that society become smart and polite. Education too constitute the method approach appropriate with disposition human have the phase stage in development.in percpective of Qor’an. Islamic education have three stage activity that are tilawah (read qor'an), tazkiyah (purify of soul) and ta'limul kitab wa sunnah (teach al-kitab and al-hikmah). Education can change jahiliyah society become the best human caused education have excess. Education have the characteristic formation of islamic comprehension intact and totality, what had been  maintenanced learning,  elaboration of science got and so that still of real syariah. The result  from islamic education will shaping calm soul, smart mind and strong physical with many generous. Islamic education compacted in ruhiyah education, fikriyah (comprehension/thought) and amaliyah (activity). The value of islamic growth in individual necessity next stage amendable to enableness in all sector human life. Potency which developed then instructed to actualized potency with entered various area life.